Seven Domains of Persisting Problems after Hospital-treated Covid-19 Indicate a Need For a Multiprofessional Rehabilitation Approach - Lovisa Hellgren; Richard Levi; Anestis Divanoglou; Ulrika Birberg-Thornberg; Kersti Samuelsson (Medical Journals Sweden, 2022)
Objectives: To identify domains of persisting problems at 4 months after discharge in patients previously hospitalized due to COVID-19, with a focus on a subgroup of patients reporting symptoms to an extent indicative of rehabilitation needs. Design: Ambidirectional observational cohort study. Patients: All patients with a laboratory-confirmed COVID-19 diagnosis admitted to hospital in a Swedish healthcare region during the period 1 March to 31 May 2020. After exclusion, 94% of all survivors (n = 433) participated in the study. Forty-three percent (n = 185) of these reported persisting problems indicating rehabilitation needs and formed a subgroup. Methods: Explorative factor analysis based on results from comprehensive telephone interviews covering persisting symptoms, including assessment of impact on daily life. Results: Seven domains were identified, comprising problems related to vision, cognition, mental fatigue, swallowing, voice, sensorimotor dysfunction, and feeling anxious/depressed. The patients in the subgroup reported a median of 8 symptoms/limitations affecting everyday life, and two-thirds reported symptoms/limitations in 3 or more domains. Conclusion: Seven problem domains corresponding to specific modalities of rehabilitative interventions were identified. A majority of patients reported problems from several domains, indicating the need for multiprofessional teams in post-COVID-19 rehabilitation. Screening of patients previously hospitalized due to COVID-19 should cover all 7 domains of persisting problems. LAY ABSTRACT More than 70% of patients with COVID-19 have previously been shown to experience 1 or several of a multitude of persisting problems several months after infection. This study aimed to identify areas of persisting problems among a broad spectrum of self-reported problems. Survivors of COVID-19 who had been discharged from hospital 4 months previously participated in a telephone interview covering persisting problems, including assessment of impact on daily life. The persisting problems clustered into 7 functional areas. Mental fatigue, cognitive- and sensorimotor problems were reported most frequently. A potential rehabilitation need was seen in more than 40% of patients interviewed. These patients reported approximately 8 different problems affecting their everyday life, and a majority of these patients reported problems from 3 or more areas. These findings highlight the need for multiprofessional teams in post-COVID-19 rehabilitation. Screening of patients previously hospitalized due to COVID-19 should cover all 7 areas of persisting problems.